Storge - Milosz, O. V. de L. (Oscar Vladislas de Lubicz), 1877-1939.; Milosz, O. V. de L. (Oscar Vladislas de Lubicz), 1877-1939.; Milosz, Czeslaw (Krakow : Wydawn. Znak, 1993)
A selection of religious poetry and essays by a Polish writer who was reared in France.